2018
DOI: 10.1128/mbio.00649-18
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic Regulation of Tumor Suppressors byHelicobacter pyloriEnhances EBV-Induced Proliferation of Gastric Epithelial Cells

Abstract: Helicobacter pylori and Epstein-Barr virus (EBV) are two well-known contributors to cancer and can establish lifelong persistent infection in the host. This leads to chronic inflammation, which also contributes to development of cancer. Association with H. pylori increases the risk of gastric carcinoma, and coexistence with EBV enhances proliferation of infected cells. Further, H. pylori-EBV coinfection causes chronic inflammation in pediatric patients. We have established an H. pylori-EBV coinfection model sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 64 publications
(88 reference statements)
0
58
2
Order By: Relevance
“…The supernatant from cell culture was collected and treated with DNAse. The viruses were concentrated by ultracentrifugation 23,500×g at 4°C for 1 h 30 min and quantified through qRT-PCR [27][28][29]. The infective dose of EBV was determined by infecting 25 × 10 4 AGS cells seeded in 6 well plates with 0, 25, 50, 75, 100, and 125 μl of the isolated virus.…”
Section: Animal Cell Cultures and H Pylori Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…The supernatant from cell culture was collected and treated with DNAse. The viruses were concentrated by ultracentrifugation 23,500×g at 4°C for 1 h 30 min and quantified through qRT-PCR [27][28][29]. The infective dose of EBV was determined by infecting 25 × 10 4 AGS cells seeded in 6 well plates with 0, 25, 50, 75, 100, and 125 μl of the isolated virus.…”
Section: Animal Cell Cultures and H Pylori Culturesmentioning
confidence: 99%
“…To evaluate differential expressions of several kinases, both direct and indirect infection methods were used [27]. In the indirect approach, the effect of proteins secreted from bacteria was assessed; and in the direct approach the kinases that are mostly affected by adherence were evaluated.…”
Section: Assessment Of Kinase Expression Through a Secretory And Adhementioning
confidence: 99%
See 1 more Smart Citation
“…It will be interesting to explore whether such mutually beneficial collaboration exists between H pylori and EBV in vivo. From a molecular perspective, previous studies showed that the virulence factor CagA from H pylori potentiated EBV‐mediated cell proliferation 72 . Similarly, EBV could inhibit protein tyrosine phosphatase SHP1, an antagonist of CagA, thereby enhancing the oncogenic action of CagA 73 .…”
Section: Future Directionsmentioning
confidence: 99%
“…The resulting SHP1 downregulation upregulates oncogenic H. pylori cytotoxin-associated gene A (CagA) phosphorylation [4]. Conversely, H. pylori CagA protein stimulates EBV-mediated epigenetic modifications and cell proliferation in a coinfection model [5]. Also, several cases show that the preceding infection of H. pylori promotes the development of EBVaGC [6].…”
Section: Introductionmentioning
confidence: 99%